EFEKTIVITAS FRAUD DIAMOND DAN FRAUD PENTAGON DALAM MENDETEKSI KECURANGAN PADA LAPORAN KEUANGAN PERUSAHAAN IDX30 YANG TERDAFTAR DI BEI 2018-2020 - Wanda Alisah Sastiana; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to see the effectiveness of the theory of fraud diamond and fraud pentagon in detecting fraudulent financial statements in IDX30 companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study was 30 IDX companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020. This research is included in the type of quantitative research because it uses secondary data. The sample of this study was taken from the population using the purposive sampling technique and obtained a sample of 18 companies with the criteria used. The results of this study are the elements of Fraud diamond and Fraud pentagon, namely Pressure (External Pressure), Opportunity (Ineffective Monitoring), Rationalization (Auditor Change), Capabilities (Director Change), and Arrogance (Frequent Number from Ceo). Simultaneously affects in detecting fraudulent financial statements, but partially elements of fraud diamond and fraud pentagon have no significant effect in detecting fraudulent financial statements in companies listed on the Indonesia Stock Exchange 2018-2020Keywords: financial statement fraud, Fraud diamond, Fraud Pentagon, Pressure, Opportunity, Rationalization, capabilities, Arrogance